Higher levels of eco-distress in psychotherapy out-patients with depressive and anxious symptoms are predicted by emotion regulation strategies - Gebhardt, Nadja; Beckord, Jil; Bäuerle, Alexander; Teufel, Martin; Friederich, Hans-Christoph; Nikendei, Christoph (Frontiers in Psychiatry, 2025)
BackgroundPsychotherapy patients are particularly vulnerable to the experience of eco-distress, often referred to as climate anxiety or eco-anxiety. Eco-distress can foster pro-environmental behavior, but its various symptoms might as well be functionally impairing and are negatively correlated with psychological well-being. The link between eco-distress and depressive and anxiety symptoms, as well as the use of dysfunctional emotion regulation strategies, may explain this vulnerability and suggest ways to promote resilience.MethodsPsychotherapy out-patients were screened at T1 (n = 203) and again five months later (T2; n = 79) for anxious (Generalized Anxiety Disorder Scale; GAD-7) and depressive symptoms (Patient Health Questionnaire; PHQ-9) and for eco-distress (Eco-Anxiety Questionnaire, EAQ-22; Generalized Anxiety Disorder Scale-Climate Version; GAD-7-C; Climate Change-Man-Made Disaster Distress Scale; CC-MMDS). Emotion regulation strategies were assessed at T1. Factorial validity was tested for eco-distress questionnaires. The relationship of eco-distress, depressive and anxious symptoms, and emotion regulation strategies was tested via multivariate models, multiple regression analysis, and mediation analysis.ResultsThe EAQ-22 and GAD-7-C showed good model fit, the factorial structure of the CC-MMDS had to be adapted. Participants who screened positive for a generalized anxiety disorder and/or a depressive disorder at T1 reported higher levels of eco-distress, but changes in anxious or depressive symptoms from T1 to T2 did not predict a change in eco-distress. At T1, Rumination and Catastrophizing predicted higher scores of eco-distress for all three questionnaires. However, emotion regulation strategies did not mediate the effect of depressive and anxious symptoms on eco-distress.ConclusionEco-distress is associated with the frequent use of the emotion regulation strategies Catastrophizing and Rumination and is higher in individuals with depressive and anxious symptoms. Addressing the use of these emotion regulation strategies in individuals could promote psychological resilience when facing the climate crisis.